Wisata Kuliner pada Wisata Bahari di Pantai Mampie Polewali Mandar Sulawesi Barat - Winowatan, Wim J; Suarta, I Putu; Rita, Rita (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The objectives of this research are (1) to find out the forms and types of culinary delights that can support marine tourism on Mampie Polewali Mandar Beach, West Sulawesi. (2) To find out strategies for developing culinary tourism to support marine tourism from the management at Mampie Polewali Mandar Beach, West Sulawesi. . The research method used is research with qualitative data type with data collection techniques using interviews, documentation and observation then analyzed using qualitative descriptive analysis techniques. The research results show that existing culinary tourism shows that there are many types of culinary available with various flavors and various forms which can actually be used as a product that can be marketed or sold in the marine tourism area of Mampie Beach, apart from that by collaborating with the local community to providing products, currently there is no culinary use so that the Mampie Beach marine tourism is not running optimally so that it is also not optimal in providing facilities and infrastructure for marine tourism. Apart from that, the importance of existing development strategies from the management as a supporter of marine tourism is known to show that the lack of initiative from the community, stakeholders and local government means that marine tourism will also continue as usual without other additional income. This is due to the lack of information obtained by the management regarding what things can support marine tourism, especially in increasing income, such as the existence of culinary tourism which will actually be a supporting thing for marine tourism at Mampie Beach.